Analysis of the Contribution of Hotel Tax and Restaurant Tax to the Regional Revenue of South Aceh Regency - Hastuti, Felda; Maulina, Rina; Marlina, Lilis; Rahmazaniati, Linda (The Future of Education Journal, 2024)
The aim of this research is to analyze how much hotel and restaurant taxes contribute to Original Regional Income in South Aceh Regency from 2016-2023. The data used in this research are primary data and secondary data obtained from BPKD South Aceh Regency from 2016-2023. This research was carried out using a qualitative descriptive method which was carried out to determine the independent variables on only one or more variables without making comparisons with other variables. The population used in this research is regional tax revenue data and the samples used are hotel taxes and restaurant taxes from 2016-2023. The data analysis used in this research is to compile an analysis table of the contribution of hotel and restaurant tax realization to PAD. The results of the research show that hotel taxes do not contribute to the original regional income of South Aceh Regency, while restaurant taxes contribute less to the original regional income of South Aceh Regency.